PENTINGNYA KUALITAS PELAYANAN KEPERAWATAN TERHADAP KEPUASAN PASIEN DI RUANG RUMAH SAKIT MENGGUNAKAN METODE LITERATURE REVIEW TAHUN 2020 - Lusia Febriyana (Nusantara Hasana Journal, 2021)
Nursing services are the main thing that must be considered, maintained and improved in accordance with applicable nursing service standards, so that consumers can experience satisfactory nursing services. The purpose of this study was to identify journals related to the importance of the quality of nursing services on patient satisfaction in the inpatient room. This study uses a literature review research design or literature review study literature review. The results of this study indicate that there is a relationship between the quality of nursing services and patient satisfaction. And among the several journals as many as 30 patients showed 26 people (86.7%) were very good. and in the unfavorable category, the results obtained from 60 patients as many as 28 people (46.7%). Many factors can influence patient satisfaction, one of which is attention, acceptance, communication and responsibility. The hospital is expected to maintain or improve its nursing services in order to minimize patient complaints and improve skills and work professionalism.